2021
DOI: 10.3390/cryst11101219
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Iron(II) and (III) in Hydroxyapatite—A Theoretical Study

Abstract: Hydroxyapatite (Ca10(PO4)6(OH)2, HAp) doped with various transition metals has generated great interest in view of its potential application in a wide variety of fields, including in catalysis as a support with a series of attractive properties. Despite a large number of experimental works devoted to the synthesis and application of iron-substituted hydroxyapatites, problems concerning the location, introduced defects, and charge compensation schemes for Fe2+ and/or Fe3+ cations in the crystal structure of HAp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Previously, for both pure HA and HA containing foreign ions, it was shown that one monoclinic cell (space group P21/b) was sufficient to reproduce the g-factors and A-hyperfine values for various paramagnetic species [57,58] and phonon spectral density [59]. It was possible to adequately describe HA systems containing foreign cations, such as aluminum, iron, and magnesium cations [18,38,60,61]. It is important to note, the descriptions of monoclinic and hexagonal cells (usually found in the experiment) use different axis notation which should not lead to confusion, as demonstrated by our results [60].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, for both pure HA and HA containing foreign ions, it was shown that one monoclinic cell (space group P21/b) was sufficient to reproduce the g-factors and A-hyperfine values for various paramagnetic species [57,58] and phonon spectral density [59]. It was possible to adequately describe HA systems containing foreign cations, such as aluminum, iron, and magnesium cations [18,38,60,61]. It is important to note, the descriptions of monoclinic and hexagonal cells (usually found in the experiment) use different axis notation which should not lead to confusion, as demonstrated by our results [60].…”
Section: Methodsmentioning
confidence: 99%
“…The morphology, stability, solubility, mechanical properties, and biological behaviors of HA synthesized in vitro are also modulated by Materials 2022, 15, 9046 2 of 12 the incorporation of foreign ions. According to their size and charge, cations, such as Na + , Zn 2+ , Mg 2+ , and Fe 3+ substitute Ca 2+ [18][19][20][21]. In contrast, anions, such as CO 3 2− , SiO 4 4− , F − , and Cl − can theoretically substitute PO 4 3− (B position) or OH − (A position) (Figure 1).…”
Section: Introduction 1hydroxyapatite's Applicationsmentioning
confidence: 99%
“…Further, the release of H + from OH − was also considered to maintain a neutral overall charge and to minimize the cell contraction caused by charge compensation. The presence of OHwithin the anion channel, surrounded by calcium ions, can show a minimal impact on the overall packing and density of the crystal [86]. In addition, they reported that Fe 3+ substitution is more reactive with the surrounding.…”
Section: Iron (Fe 2+ and Fe 3+ )mentioning
confidence: 99%
“… Hydroxyapatite unit cell. Color coding: phosphorus—orange, oxygen—red, hydrogen—light grey, Ca(1)—purple, Ca(2)—blue [ 11 ]. …”
Section: Figurementioning
confidence: 99%
“…Substitutions in the apatite structure have been developed for a wide range of biomedical applications, such as bone repair and tissue regenerations; bioactive and/or antibacterial coating for medical devices, biomarkers, or carriers in drug/gene delivery systems; and biomagnetic agents for cancer treatment [ 10 ]. These properties are due to the unique structural characteristics of HA, the unit cell of which is represented in Figure 1 [ 11 ]. HA belongs to the class of minerals whose composition has a general formula: M 10 (ZO 4 ) 6 X 2 , where M is one-, two-, three-valent cations (K + , Ca 2+ , Sr 2+ , Ba 2+ , Pb 2+ , Na + , Mn 2+ , Mg 2+ , Th 3+ , Ni 2+ , etc.…”
Section: Introductionmentioning
confidence: 99%